THE RELATIONSHIP BETWEEN THE SHOCK INDEX AND EARLY CLINICAL OUTCOMES IN PATIENTS WITH SEPSIS IN THE EMERGENCY DEPARTMENT: HUBUNGAN ANTARA SHOCK INDEX DAN LUARAN KLINIS AWAL PADA PASIEN SEPSIS DI INSTALASI GAWAT DARURAT - Melvin Andrean; Jennifer Rose; Rifky Budi Triyanto (Faculty of Medicine Universitas Islam Sumatera Utara, 2027)
Sepsis remains a major cause of morbidity and mortality worldwide, with early clinical deterioration frequently occurring within the first hours of emergency department (ED) presentation. This retrospective cohort study evaluated the association between admission shock index and early clinical outcomes in 200 adult ED patients with sepsis, operationally defined as qSOFA ≥2 with suspected infection, presenting between January and December 2025. Admission shock index was calculated from triage vital signs and analyzed as a continuous variable scaled per 0.1-unit increase. Early outcomes within 24 hours included mortality, vasopressor requirement, and ICU/HCU admission. Bivariate and multivariable logistic regression and ROC curve analyses were performed. The mean admission shock index was 0.92 ± 0.27. Higher shock index was independently associated with increased mortality (AOR 1.41, 95% CI 1.24–1.61; p=0.001) and vasopressor requirement (AOR 1.38, 95% CI 1.21–1.58; p=0.001). The shock index demonstrated acceptable discriminatory ability for mortality (AUC=0.721) and vasopressor requirement (AUC=0.718), with an optimal cut-off of SI ≥0.95. No significant association was found with ICU/HCU admission (p=0.222). Admission shock index may serve as a simple bedside indicator for early risk stratification in ED sepsis patients.